Involving parents from the start: formative evaluation for a large randomised controlled trial with Botswana Junior Secondary School students. Issue 1 (25th March 2016) - Vig, Jessica; Miller, Kim S.; Chirwa-Motswere, Catherine; Winskell, Kate; Stallcup, Elizabeth
Abstract : While HIV prevention research conducted among adolescent populations may encounter parental resistance, the active engagement of parents from inception to trial completion may alleviate opposition. In preparation for implementing a large randomised controlled trial (RCT) examining the efficacy of a behavioural intervention targeting adolescent sexual risk behaviours, a formative evaluation was undertaken to assess parental reactions to the proposed trial. Six focus groups were conducted with parents of adolescents (aged 13–17) from rural, peri-urban and urban junior secondary schools in Botswana. Focus groups explored comprehension and acceptability among parents of the forthcoming trial including HSV-2 testing, the return of results to the adolescent (not the parent), trial information materials and the parental consent process. Parents welcomed the study and understood and accepted its moral and ethical considerations. Their reactions regarding return of HSV-2 results only to adolescents (not the parent) were mixed. Parents understood the consent process and most agreed to consent, while indicating their desire to remain informed and involved throughout the RCT. The focus group discussions (FGDs) provided valuable information and insights that helped strengthen the study. As a result of parents' feedback, counselling procedures were strengthened and direct linkages to local services and care were made. Informational materials were revised to increase clarity, and materials and procedures were developed to encourage and support parental involvement and parent–child dialogue. Ultimately, parental feedback led to a decision by the Government of Botswana to allow parents to access their child's HSV-2 test results.